Characteristics of Titounis Children Songs: A Study of Songs, Music Instruments and Onomatopoeia - Wafa, Mochammad Usman; Purwani, Neli; Malik, Abdul (Harmonia: Journal of Arts Research and Education, 2020)
The purpose of the study is to describe an analysis of children’s song characteristics Titounis. This study used a musicological approach to recognize songs’ characteristics. The data collection were document study and, listen and take note. This study used a content analysis technique. The analysis cover three aspects: (1) songs’ analysis, (2) instruments’ analysis, (3) Onomatopoeia. The songs that were analyzed were (1) Petit Escargot, (2) Le Roues de l Autobus, (3) Les Chiffres, (4) Un kilometer en Roulant. In the song analysis, the patterns used were general patterns, using fun and cheerful vocals, strong tonal stress, relatively limited variations in tones, slow, fast, and gradual tempo. The delivery style invites singing as well as dialogue or interaction. Then in musical instruments, the melody variations of each instrument form harmonization, the use of non-musical instruments emphasizes the theme of the song and provides the experience of hearing about the environment. The onomatopoeic analysis shows sound vroom (car), pataboum (jumping passengers), bip-bip-bip (serine), suisse-suisse (wiper). The onomatopoeia of Titounis songs serves to strengthen the song’s theme.